Optimization of Sipirok Woven Fabric Production Using Fuzzy-Multi Objective Linear Program - Nurjanna, Nurjanna; Rakhmawati , Fibri (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The Sipirok woven fabric industry is one of the industrial characteristics of South Tapanuli Regency in North Sumatra. In general, the challenges encountered in the industry are related to production optimization. There have been numerous research on production optimization that use mathematical methods such as the simplex method. However, the simplex technique has limits, as it only has one objective function. As a result, the Fuzzy Multi-Objective Linear Program method is employed in this study. Because Fuzzy Multi-Objective linear program includes two objective functions, maximizing profits and reducing/minimizing processing time, it can be used to tackle optimization issues in the Sipirok woven fabric company. This sort of research employs primary data, specifically interviews and direct observation at the research site, the Sipirok Woven Fabric Industry. This study's calculations were supplemented by the simplex method, which was then followed by the two-phase simplex method to generate the ultimate outcome of woven fabric manufacture. The woven fabric industry now produces 472 units of Samuel's woven fabric, with a maximum profit of Rp. 37,920,000 and a minimum processing time of 7,110 hours, where the variable value λ is 0.10 to represent the maximum degree of each objective function.